2018
DOI: 10.1111/dar.12670
|View full text |Cite
|
Sign up to set email alerts
|

The effect on emergency department visits of raised alcohol minimum prices in Saskatchewan, Canada

Abstract: The minimum pricing policy change led to a lagged decrease in motor vehicle-collision-related ED visits for women older than 25. Of note, there did not appear to be an instantaneous effect on the rate of alcohol-related injury ED visits immediately after the policy implementation nor lagged effects for other gender-age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 18 publications
0
22
1
Order By: Relevance
“…As individuals in lower socioeconomic status experience the highest rates of alcohol attributable ill health and premature death,55 they are likely to benefit most from the policy implementation 29. Empirical published data relating to the Canadian provinces that have implemented and evaluated MUP, report impacts on reduced alcohol related morbidity,56 mortality,12 crime,57 and healthcare use,1358 particularly for lower income groups. NHS Health Scotland’s commissioned evaluation will focus specifically on assessing the impact of MUP on harmful drinkers, and will use primary qualitative and quantitative data collection from users and providers of alcohol treatment services, as well as secondary analyses of KWP data 34.…”
Section: Discussionmentioning
confidence: 99%
“…As individuals in lower socioeconomic status experience the highest rates of alcohol attributable ill health and premature death,55 they are likely to benefit most from the policy implementation 29. Empirical published data relating to the Canadian provinces that have implemented and evaluated MUP, report impacts on reduced alcohol related morbidity,56 mortality,12 crime,57 and healthcare use,1358 particularly for lower income groups. NHS Health Scotland’s commissioned evaluation will focus specifically on assessing the impact of MUP on harmful drinkers, and will use primary qualitative and quantitative data collection from users and providers of alcohol treatment services, as well as secondary analyses of KWP data 34.…”
Section: Discussionmentioning
confidence: 99%
“…We combined all chronic and acute alcohol-related conditions as a whole rather than acute injuries covered elsewhere. 28 Our data show that less than 1% of all attendees in both Scotland and England were diagnosed with partially acute injuries; as such, it was not possible to analyse acute partially alcohol-related diagnosis separately. However, our research provides further evidence that there was no immediate association between MUP and changes in the prevalence of alcohol-related diagnosis among ED attendees.…”
Section: Key Resultsmentioning
confidence: 70%
“…Existing studies have suggested MUP led to a reduction in alcohol-attributable hospital admissions and alcohol-related deaths, [25][26][27] but there was no immediate effect on ED attendances for alcohol-related injury in Canada. 28 These studies focus on alcohol-related admissions and attendances based on patients' diagnosed diseases and injuries. Our study, on the other hand, examined alcohol-related attendances based on the nurse interviewers' observations and attendees' self-reported behaviours.…”
Section: Key Resultsmentioning
confidence: 99%
See 2 more Smart Citations